Tariff of Indonesia Case Based Groups (INA-CBG’s) and Real Tariff on Acute Gastroenteritis Patient National Health Insurance in Inpatient Unit Class I District General Hospital Undata Palu - Nur Mila Sari; Miftahul Haerati Sulaiman; Khairunisaa; Nur Azizah Azzahra; Muh. Ryman Napirah; Indra Eka Wardana Toii (Universitas Muhammadiyah Palu, 2024)
Hospitals are required to provide tariffs that can be reached by the general public. This cost of service problem becomes very important so as to encourage all elements concerned, to calculate in real how much the cost of hospital services. Undata Palu Public Hospital has never done real tariff calculation analysis by hospital, where the difference or comparison result will show how exactly impact of INA-CBG's tariff payment system on finance or hospital income. The purpose of this study is to see and know the difference between INA-CBG's tariff and real hospital tariff in GEA patients of JKN participants in the first class hospital unit of Undata Palu Public Hospital. This research type is quantitative with descriptive method. Data were retrospectively taken from BPJS claim files and medical records of patients. The research object was medical record of inpatient with diagnose of Acute Gastroenteritis (GEA) at Undata Hospital with code of INA-CBG's K-4-17-I and K-4-17-II period January - September 2017. The difference between the INA-CBG's tariff and the real tariff of the hospital by the total difference between the INA-CBG's tariff and the real tariff of the hospital is Rp. 38,515,292, for total INA-CBG's tariff of Rp. 127,432,300 and the real rate of hospital is Rp. 88,917,008. So overall it shows that INA-CBG's tariff is higher than the real rate in hospital. It is recommended to calculate the difference between INA-CBG's tariff and the real tariff of hospitals with different cases, so as to know the applicable cross subsidies between diseases that are beneficial and detrimental to the hospital.